2013
DOI: 10.1007/s11248-013-9726-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel chloroplast transformation vector compatible with the Gateway® recombination cloning technology

Abstract: To analyze the suitability of Gateway(®) vectors for transformation of chloroplasts, we converted a standard plastid transformation vector into a Gateway(®) destination vector containing the necessary recombination sites attR1 and attR2. Insertion of the green fluorescent protein (GFP) coding sequence with associated T7g10 ribosome binding site into this destination vector created the expression vector for transformation of tobacco chloroplasts with the biolistic method. Correct integration of the transgene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…One method used the Gateway system for construction of chloroplast vectors to simplify vector construction and improve vector design [28]. Another group used modular design of genetic elements to construct chloroplast vectors to build transcriptional units as well as target any homologous recombination site of choice [29].…”
Section: The Art Of Chloroplast Genome Engineering – Evolving New Conmentioning
confidence: 99%
“…One method used the Gateway system for construction of chloroplast vectors to simplify vector construction and improve vector design [28]. Another group used modular design of genetic elements to construct chloroplast vectors to build transcriptional units as well as target any homologous recombination site of choice [29].…”
Section: The Art Of Chloroplast Genome Engineering – Evolving New Conmentioning
confidence: 99%
“…For the intermediary vector pMA‐lettuce, the sequences corresponding to the trnI and trnA region of the Lactuca sativum plastid genome (Ruhlman et al ., ) flanked by Kpn I and Sac II restriction sites were custom synthesized and introduced into the company's standard backbone vector (GeneArt, Germany). In order to create pDEST‐PN‐L, the complete Gateway ® cloning cassette together with the aadA expression cassette was excised from pDEST‐PN‐T (Gottschamel et al ., ) and inserted into pMA‐lettuce using the restriction enzymes Kpn I and Sac II. The sequence of the synthetic fusion gene ( ediii ‐1‐4) consists of all four DENV‐EDIII sequences (order: ediii ‐1, ediii ‐3, ediii ‐4, ediii ‐2) linked by penta‐glycine linkers (Etemad et al ., ; Gottschamel et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…In these vectors, the transgene is controlled by the strong tobacco plastid rRNA operon promoter (Prrn; Svab and Maliga 1993) fused with the 5 0 UTR of gene 10 from bacteriophage T7 and the 3 0 UTR of the plastid rbcL gene. The Gateway Ò -compatible plastid transformation vector pDEST-T7 was obtained by excision of the Prrn promoter sequence (Ye et al 2001) from plasmid pDEST-PN-T (Gottschamel et al 2013). The exclusive presence of the phage T7-derived promoter (Tabor and Richardson 1985) in the new vector was confirmed by sequencing.…”
Section: Vector Constructionmentioning
confidence: 99%
“…Several vectors for transient or stable plant transformation (Buntru et al 2013;Dubin et al 2008Dubin et al , 2010Earley et al 2006;Karimi et al 2007Karimi et al , 2013Lyska et al 2013) have been reported including a plastid transformation vector for constitutive transgene expression (Gottschamel et al 2013).…”
Section: Introductionmentioning
confidence: 99%